Analisis Terhadap Penerapan Projek Penguatan Profil Pelajar Pancasila (P5) di Kelas VIII SMP Pertiwi 2 - Pribadi, Faris Alfarizi; Yeni J, Fetri; Hidayati, Abna; Amsal, Mutiara Felicita (Indo-MathEdu Intellectuals Journal, 2024)
Education is a key pillar of national development, and innovations such as the Merdeka Curriculum aim to improve the quality of education in Indonesia by giving freedom to schools and teachers. This study evaluates the implementation of the Merdeka Curriculum, specifically the Pancasila Student Profile Strengthening Project (P5) at SMP Pertiwi 2 Padang. The focus of the study is to assess the effectiveness of P5 in developing students' creative thinking and identifying influencing factors. This study uses a qualitative approach with a case study design to evaluate the implementation of the Pancasila Student Profile Strengthening Project (P5) at SMP Pertiwi 2 Padang. Data were collected through participatory observations, in-depth interviews with teachers, students, and principals, and documentation studies. Data analysis was carried out in a qualitative descriptive manner with the stages of data reduction, data presentation, and conclusion drawn. The results of the study show that in general, P5 has made a positive contribution in developing student creativity. However, there are still several aspects that need to be improved, such as improving planning, material enrichment, and the availability of facilities. In addition, this study also identifies several factors that affect the successful implementation of P5. The findings of this study are expected to provide recommendations for schools, teachers, and policymakers in an effort to increase the effectiveness of the implementation of the Independent Curriculum in the context of P5